THE PSYCHOLOGY OF FALSE CONFESSIONS: INVESTIGATING THE COGNITIVE AND EMOTIONAL FACTORS BEHIND INVOLUNTARY ADMISSIONS - Lucy Lidiawati Satioso; Sarah Williams; Jessica Green (World Psychology, 2026)
False confessions have long been a concern in the criminal justice system, yet the cognitive and emotional factors that drive individuals to confess to crimes they did not commit remain insufficiently explored. This research investigates the psychological underpinnings of false confessions, focusing on the cognitive overload and emotional stress experienced by suspects during interrogations. The study aims to examine how these psychological factors contribute to involuntary admissions and how they can be mitigated to prevent wrongful convictions. A mixed-methods approach was employed, combining qualitative interviews with legal professionals, psychologists, and law enforcement officers, along with a case study analysis of documented false confession cases. The findings reveal that emotional stress, particularly fear and anxiety, combined with cognitive overload during prolonged interrogations, significantly increases the likelihood of false confessions. The study concludes that false confessions are not solely the result of coercive interrogation techniques but are also deeply influenced by emotional and cognitive vulnerabilities. The research suggests the need for reform in interrogation practices, including better psychological safeguards and more effective legal protections for suspects.